THE MEDIATING ROLE OF CONSUMER ETHNOCENTRISM IN THE LINK BETWEEN SERVICE QUALITY, BRAND REPUTATION AND ETAILQ TOWARD CUSTOMER SATISFACTION ON GOJEK’S CUSTOMERS - Iskandar, Donant Alananto; Wahyudi, Triyono Arief (Economic Faculty, Attahiriyah Islamic University, 2020)
This research is a quantitative associative type that discusses the effect of service quality, brand reputation, and etailq on customer satisfaction and consumer ethnocentrism as a mediating variable. The object of this research is people who ever use application and use Gojek services at least 3 (three) times since the study began, that is October 2018 until August 2019 in Jakarta, Bogor, Depok, Tangerang, Bekasi (Jabodetabek). The test used is a statistical test using the SPSS program that is a test of normality, validity, reliability, classic assumptions, hypotheses, determination, multiple regression and path analysis to see the intervening variable whether it indirectly affect independent variables toward dependent variable or independent variables directly affect the dependent variable. The result of this article is consumer ethnocentrism indirectly affects the influence between service quality, brand reputation, and etailq toward customer satisfaction on Gojek’s customers in Jabodetabek.